Report of the Key Opinion Leaders Meeting on Stem Cell-derived Beta Cells. Issue 8 (August 2018) - Odorico, Jon; Markmann, James; Melton, Douglas; Greenstein, Julia; Hwa, Albert; Nostro, Cristina; Rezania, Alireza; Oberholzer, Jose; Pipeleers, Daniel; Yang, Luhan; Cowan, Chad; Huangfu, Danwei; et al.
Abstract : Abstract: Beta cell replacement has the potential to restore euglycemia in patients with insulin-dependent diabetes. Although great progress has been made in establishing allogeneic islet transplantation from deceased donors as the standard of care for those with the most labile diabetes, it is also clear that the deceased donor organ supply cannot possibly treat all those who could benefit from restoration of a normal beta cell mass, especially if immunosuppression were not required. Against this background, the International Pancreas and Islet Transplant Association in collaboration with the Harvard Stem Cell Institute, the Juvenile Diabetes Research Foundation (JDRF), and the Helmsley Foundation held a 2-day Key Opinion Leaders Meeting in Boston in 2016 to bring together experts in generating and transplanting beta cells derived from stem cells. The following summary highlights current technology, recent significant breakthroughs, unmet needs and roadblocks to stem cell–derived beta cell therapies, with the aim of spurring future preclinical collaborative investigations and progress toward the clinical application of stem cell–derived beta cells. Abstract : Summary highlights of the 2-day Key Opinion Leaders Meeting in Boston 2016, that brought together experts in generating and transplanting beta cells derived from stem cells.